Bubbles slipping along a crenelated wall. (4th November 2016) - Germain, D.; Le Merrer, M.
Abstract: We describe the ascent dynamics of air bubbles squeezed against a rigid crenelated plate immersed in a liquid bath. Depending on its shape and the inclination angle, the bubbles can remain trapped in the crenelations, or slip against the wall. In particular, the yield force separating the two regimes increases with the height of the crenels. In the second regime, the slipping motion is characterized by a capillary number which barely depends on the crenel geometry (wavelength and amplitude), at large enough angles. We finally discuss the regime of intermediate angles, and interpret the measured oscillations in bubble velocities through the existence of a (spatially) periodic force. These results provide information at the bubble scale for processes at play in the slip of foams and emulsions against rough walls.